2013 3rd IEEE International Advance Computing Conference (IACC) 2013
DOI: 10.1109/iadcc.2013.6514246
|View full text |Cite
|
Sign up to set email alerts
|

PPN: Prime product number based malicious node detection scheme for MANETs

Abstract: A mobile adhoc network is an autonomous network that consists of nodes which communicate with each other with wireless channel. Due to its dynamic nature and mobility of nodes, mobile adhoc networks are more vulnerable to security attack than conventional wired and wireless networks. One of the principal routing protocols AODV used in MANETs. The security of AODV protocol is influence by malicious node attack. In this attack, a malicious node injects a faked route reply claiming to have the shortest and freshe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The X-axis of the graph represents Number of nodes and Y-axis represents the Network Throughput. The graph demonstrates that AODV routing protocol with proposed method always perform better than standard base method given in paper [13]. The results of the experiments showed that in the presence of 4-10% malicious node,.…”
Section: Simulation Results and Comparison 41 Simulationmentioning
confidence: 65%
See 1 more Smart Citation
“…The X-axis of the graph represents Number of nodes and Y-axis represents the Network Throughput. The graph demonstrates that AODV routing protocol with proposed method always perform better than standard base method given in paper [13]. The results of the experiments showed that in the presence of 4-10% malicious node,.…”
Section: Simulation Results and Comparison 41 Simulationmentioning
confidence: 65%
“…However, once the information packets arrive, the malicious node discards them. To preventing malicious node attack, paper [13] presents PPN (Prime Product Number) theme for detection and removal of malicious node.…”
Section: Related Workmentioning
confidence: 99%
“…But, when data packets arrive, malicious nodes discard them. To prevent malicious node attack, PPN (Prime Product Number) scheme was presented to detect and remove malicious node by Gambhir and Sharma [13]. Active Peer-to-Peer (P2P) worms attack neighbour peers based on a hit-list and pose a threat to both P2P network and Internet.…”
Section: Related Workmentioning
confidence: 99%
“…Source node (SN) broadcast RREQ to destination and in response intermediate node (IN) wishing to send RREP has to provide product of all prime numbers (PPN) from destination to source and also information of its cluster head. Upon receiving the RREP message from IN, SN with the help of its cluster head (CH) will divide the PPN with the Node IDs stored in neighbor table at CH to see whether IN is its reliable node [6]. If PPN is fully divisible, then intermediate node is a reliable node, else it is malicious node and CH adds it to malicious list and broadcast it to whole network to remove it from the routing table.…”
Section: Ppn: Prime Product Number Based Malicious Node Detection Schmentioning
confidence: 99%
“…The method of detection and removal of malicious node by using prime product number (PPN) is used in [6]. In this scheme each node has unique prime number.…”
Section: Ppn: Prime Product Number Based Malicious Node Detection Schmentioning
confidence: 99%